Active recovery effects on local oxygenation level during intensive cycling bouts - Koizumi, K.; Fujita, Y.; Muramatsu, S.; Manabe, M.; Ito, M.; Nomura, J. (Journal of Sports Sciences, 2011)
We hypothesised that the oxygen supply to the fatigued muscles is improved after the recovery with exercise caused by aerobic metabolism in the slow twitch fibres during the recovery period. Ten males performed a 30 s maximum cycling (1st Exercise), followed by a 20 min rest interval (Interval Rest) in which participants were either sitting (No Exercise) or low intensive cycling (Active). Then they again underwent a 30 s bout of maximum cycling (2nd Exercise). The total work of the 2nd Exercise was higher in Active compared to No Exercise (297 ± 14 vs 276 ± 23 J · kg-1, P < 0.01). After Interval Rest, the muscle oxygenation level (P < 0.05) and blood lactate concentration (P < 0.05) were lower in Active compared to No Exercise. In Active, the total work was higher in the 2nd Exercise than the 1st Exercise (297 ± 14 vs 277 ± 23 J · kg-1, P < 0.01), and muscle oxygenation levels during the 2nd Exercise were also higher at 10 (P < 0.05) and 15 (P < 0.01) s after the beginning of the exercise. It was suggested that active recovery exercise would manage to increase the muscle oxygenation level, and improve the performance during the 2nd Exercise accompanied with blood lactate control.